Malignant melanoma: sistemic chemotherapy - D'Auria, Agustín (Cirugía del Uruguay, 1974)
Systemic chemotherapy has shown to be of little usefulness in the treatment of malignant melanoma. Its use has been confined to cases of disseminated disease. Many drugs have been tried, but objetive remissions have been scarce. The best drug until the present time has been DTIC or imidazole-carboxamide. In our hands it is given at a dosis of 200 mgm per square meter, five days in a row. Clinical investigations are being performed on prophylactic chemotherapy in patients with positive ly..!Ilph nodes. Prophylactic immunotherapy is also studied in the same type of patients. These investigations are sponsored by the W.H.0. Time is needed to appraise the results of these experiences.